Impact of plant population and weed management practices on the performance of Basmati Rice - Jacob D (Department of Agronomy, College of Agriculture, 2002)
A field experiment was conducted at the Instructional Farm, College of Agriculture, Vellayani during the mundakan season of 200/-2002 in order to determine the effect of spacing and weed management practices on the yield of scented basmati rice cv. Pusa Basmati-I. The field experiment was laid out in Randomised Block Design with two factors, in fifteen treatment combinations and three replications. The factors included were spacings viz. 15 x ] 5 cm (S,). 20 x 10 cm (S2) and 15 x 10 cm (S3) and weed management practices viz. anilofos + 2,4-D EE at 6 OAT followed by hand weeding at 20 DAT (Wi), anilofos + 2,4-0 EE at 6 OAT followed by 2,4-D sodium salt at 20 DA T (W2), hand weeding twice at 20 and 40 DA T (Wl). weed free check 0N4) and unweeded control 0Ns). Transplanting basmati rice at 20 x 10 cm, which is the recommended spacing for medium duration rice in Kerala, enhanced the growth characters of rice such as plant height, tiller count and leaf area index. Dry matter production and nutrient uptake of rice were also enhanced by this spacing. The count of grasses, sedges and broad leaved weeds and the total weed population was reduced by this practice resulting in higher net income and benefit-cost ratio. The dry matter production of weeds and nutrient uptake by weeds were also significantly lower at this spacing compared to the other two spacings Adoption of pre-emergence application of anilofos + 2,4-D EE @ 0.4 + 0.53 kg ai ha" at 6 DAT followed by 2,4-D sodium salt @ ] kg ai ha-' at 20 DAT resulted in enhanced plant height. tiller count, leaf area index. dry matter production and nutrient uptake of rice. The yield attributes and grain yield were significantly increased by this practice and the weed index was significantly reduced. The total weed population, weed dry matter production and nutrient uptake were also reduced and weed control efficiency was increased by this treatment. The treatment combination involving recommended spacing of 20 x 10 cm and pre-ernergence application of anilofos + 2,4-D EE @ 0.4 + 0.53 kg ai ha" at